Petani Sawit Remaja di Desa Koto Ranah Kecamatan Kabun Kabupaten Rokan Hulu - Maulani, Iffah; Yusuf, Yusmar (Journal of Management Education Social Sciences Information and Religion, 2025)
This research aims to understand the phenomenon of career choices among youth as palm oil farmers in Koto Ranah Village, Kabun District, Rokan Hulu Regency. Many young people, especially young men, opt to work in the agricultural sector, particularly palm oil farming, despite the importance of higher education. The primary data collection method employed in this study was descriptive qualitative interviews. The results show that several factors influence the decision of youth to work as palm oil farmers. First, family profession inheritance plays a significant role, with many young individuals viewing this job as a continuation of family tradition. Second, the limited job opportunities in the village push youth to choose occupations that are considered more realistic and profitable. Third, the interests and skills possessed by the youth in agriculture contribute to their decision. Additionally, the availability of land and limited access to higher education are crucial factors in determining career choices. This research provides insights into how the cultural, social, and economic contexts in Koto Ranah Village shape youth perspectives on education and careers. The findings are expected to serve as a reference for policymakers and stakeholders in formulating programs that can increase youth interest in pursuing higher education and expand job opportunities in other sectors.